Pembuatan Dan Karakterisasi Krim Tabir Surya Berbahan Aktif Ekstrak Etanol Daun Suruhan (Paperamia Pellucida (L). Kunth) - Esi Agnesa; Dinda Fransiska.D. N; Indri Anggraini; Aldi Reviansyah; Charles Banon (Jurnal Multidisiplin Dehasen (MUDE), 2023)
Skin that is continuously exposed to ultraviolet rays from the sun can experience damage such as sunburn (reddish skin), tanning (brown skin), photoaging (premature aging), photocarcinogenesis (uneven skin pigment) and skin cancer. Sunscreen is a cosmetic preparation used to protect the skin from exposure to sunlight, especially ultraviolet (UV) which can absorb, scatter and reflect UV rays. Order leaves from the Piperaceae family contain flavonoids, alkaloids, tannins and phenols. Phenolic compounds, especially the flavonoid group, have potential as sunscreens because of the chromophore group which is able to absorb UV rays, both UV-A and UV-B, thereby reducing their intensity on the skin. This research was conducted to determine the formulation and determine the SPF (Sun Protection Factor) value in vitro. Tabir suya with ethanol extract of suruhan leaves is made with 3 formulations and tested organoleptically, homogeneity, pH, and Absorption Test. Calculation of SPF using UV-VIS spectroscopy using a wave length of 290-320 nm and SPF values tested in vitro and calculated using Mansur calculations are A1= 1.82134, A2= 4.54284, A3= 5.70566. The SPF values A2 and A3 are included in the good cream category according to SNI.